Moderasi Beragama di media : (Perspektif Dakwah) - Al Jauzi, M. Seneng; Hamidah, Lilik (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2023)
This journal aims to explore the role of da'wah in moderating religious practices through the mass media. In this increasingly advanced digital era, the mass media has become the main channel for conveying information and communicating with the public. This article looks at the important role that da'wah plays in bridging between cool religious messages and moderate religious practices in the media. The findings of this study indicate that da'wah plays an important role in reducing tensions and religious conflicts in the mass media. Through an approach that focuses on education and understanding, da'wah can transform negative narratives into messages that are more harmonious and inclusive. In addition, da'wah is also able to promote inter-religious dialogue, respect differences, and build strong brotherhood among adherents of different religions. This journal makes an important contribution in understanding the role of da'wah in moderating religious practices through the media. The implication of this research is the importance of strengthening the role of da'wah in encouraging a moderate religious perspective, maintaining diversity, and preventing religious extremism. It is hoped that this research can become the basis for the development of a more effective da'wah strategy in dealing with the challenges of mass media in today's digital era.